Association Between Smartphone Use and Insomnia Incidence in Youth: A Meta-Analysis - Kurniawan, Rezza Debby; Muhzal, Murni; Putri, Anggy Yulistya; Allo, Caecilia Bintang Girik; Fitri, Dina Jumiatul (Jurnal Matematika, Statistika dan Komputasi, 2026)
Smartphone use has become an integral part of young people's lives (adolescents/students). However, excessive use is often associated with the incidence of insomnia. Various studies have been conducted to examine this relationship, but they have produced varying risk magnitudes. Meta-analysis can be used to quantitatively summarize the impact of smartphone use on the incidence of insomnia in young people. This study uses data from three cross-sectional journals published between 2022 and 2024, comprising a total of 371 respondents, that met the PICO criteria. The calculation of summary effect sizes used the random effect model because the results of the studies used came from different researchers, which was also confirmed by a substantial heterogeneity value (I² = 80.0%). The effect size used is the Risk Ratio (RR). The pooled analysis results showed that excessive smartphone use significantly increased the risk of insomnia. The obtained Summary Risk Ratio (RR) was 2.6199 (95% CI: 1.0791 – 6.3609). These results interpret that the risk of insomnia in young people with excessive smartphone use is 2.6199 times higher compared to normal use. Thus, smartphone use is a significant risk factor for the incidence of insomnia in young people